PEMBERDAYAAN KELOMPOK TANI MENGOLAH LIMBAH JAGUNG MENJADI PAKAN TERNAK - Toto Toto; M. Arief Rizki Mauladi; Rian Kurnia (Jurnal Abdi Insani, 2026)
The Bungur Farmer Group in Panyingkiran Village faces limited water availability on rainfed land, allowing them to cultivate only corn as their main commodity. Although corn production is relatively good, corn cob waste has not been optimally utilized. This program also supports the government’s initiatives related to food security.This community service program aims to enhance the knowledge and skills of group members in processing corn cob waste into economically valuable livestock feed through the application of appropriate technology. It also seeks to strengthen institutional capacity and empower human resources in managing the organization effectively. he implementation methods include socialization, technical training on the use of corn shelling and cob-chopping machines, waste processing through fermentation and silage techniques, as well as managerial assistance. The activities were carried out using a participatory approach to ensure that farmers were directly involved in the practice and application of the technology, involving 20 members of the Bungur Farmer Group. The results show a significant improvement in the skills and awareness of farmer group members. They are now able to process corn cobs into high-quality fermented and silage livestock feed, reduce agricultural waste, lower dependence on commercial feed, and create new business opportunities in the livestock sector. The program also strengthened the farmer group’s institutional capacity and expanded the marketing network for processed feed products. The training effectively enhanced the capacity of farmer group members, created added economic value, and supported sustainable agricultural development in line with the Sustainable Development Goals (SDGs).